Implementation of The Use Maternal and Child Health (MCH) Handbook (Edukasi, 2022)
Health is one of the things that must reck in fulfill of child development. The aims the study is to find out implementation of the use Maternal and Child Health (MCH) Handbook in BKB PAUD Teratai Putih, Kuningan, South Jakarta. This research used a phenomenological qualitative method. This subject is the research were 1 principal, 3 teachers and 3 mothers in BKB PAUD Teratai Putih. The result of this study showed that (1) The three teachers and mothers (parents of students) BKB PAUD Teratai Putih very well know the MCH Handbook, they can apply the MCH Handbook according to the instructions. (2) The MCH Handbook is implemented in the activities of visits to posyandu, visits of health workers to schools, habituation of the clean and healthy behavior, school promotion and child development reports, reporting of child development achievement levels and parenting using the MCH Handbook as an information tool, monitoring growth and development. children, recording health services and communication tools, (3) Supporting factors in implementing the use of the MCH Handbook are cadres who are also teachers to make communication easier so that they can work together with parents in caring for and developing children's growth and development and one of the inhibiting factors is when There are parents who do not bring the MCH Handbook during the posyandu activities because they are missing or damaged.